Application of Total Mixture Forages Silage on Sheep Farming: Bean Sprouts Addition and Controlled Internal Drug Release Vaginal Insertion on Sheep Reproduction - Bachruddin, Zaenal (Faculty of Animal Sciences Universitas Gadjah Mada, 2014)
The long run objective of study is the optimization of local resources mainly local forages as feed and local animal as genetic resources. Twenty seven local sheep were divided into three groups. Group I (TO) were feed with total mixture forages silage (TMFS) by inoculation of Lactobacillus plantarum, without beansprouts addition; Group II (PI) as the same group I with addition of 250 g/animal daily of beansprouts; and Group III (PII) as the same group I with addition of 500 g/animal daily of beansprouts. After one month, all animal was fed by TMFS with or without beansprouts addition;four animals in each group were treated for 12 days by Controlled Internal Drug Release (CIDR) vaginal insertion. All animals were identified by ear tag and bred naturally using a ram. The results of the study showed that quality of TMFS respectively as follow: Dry Matter (DM %), crude protein (CP %), Crude Fibre (CF %) and pH is 30.40, 12.35, 22.5 and 3.92. While the TMFS consumption for each group respectively as follow: P0, PI and PII are 2.01, 2.00 and 2.02 kg per animal daily. The result of in vivo study of beansprouts addition and CIDR insertion into animal that were fed by TCFS showed that percentage of pregnancy of the animal tend to be higher with CIDR insertion (66%) compares to without CID Rinsertion (40%). However the beansprouts addition into TCFS improved the animal delivered an ewe and the number of young animal increase as well due to bean sprouts addition.